Review on the occurrence and profiles of polybrominated diphenyl ethers in the Philippines. (December 2015) - Mackintosh, Susan A.; Wallace, Joshua S.; Gross, Michael S.; Navarro, Denise D.; Pérez-Fuentetaja, Alicia; Alaee, Mehran; Montecastro, Doris; Aga, Diana S.
Abstract: The environmental occurrence of polybrominated diphenyl ethers (PBDEs) has been a subject of concern for the past decade because they are persistent, bioaccumulative, and toxic. These compounds have been listed as persistent organic pollutants (POPs) by the Stockholm Convention and are expected to disperse in the global environment even after their use and production. While the occurrence of PBDEs has been well characterized in environmental and biological samples from North America, Europe, and some Asian countries (i.e. China, Japan, and Korea), there is a scarcity of available data in developing Asian countries, such as the Philippines. Examination of PBDE contamination in the Philippine environment is particularly important because regulations have only recently been implemented on the production and use of PBDEs in this country. Additionally, the Philippines receives e-waste from Western countries, which is becoming a major source of organic contaminants in the tropical Asian regions. Ultimately, the Philippines may be a hot spot for contributing to on-going global PBDE pollution due to long-range atmospheric transport. This paper presents a review of the available literature on PBDEs in both environmental and biological samples collected from the Philippines. It is also intended to provide an overview on the levels and congener profiles of PBDEs in samples from the Philippines and to compare these data with other Asian countries. New data are presented on PBDE occurrence and congener profiles in fish commonly consumed by Filipinos and in particulate matter samples collected in Metro Manila, the capital of the Philippines. Both studies contribute to the available knowledge of PBDEs in the Philippines. We aim to stress the importance of future studies in countries receiving e-wastes, such as the Philippines, and suggest what future directions might be taken to enhance the available data on the presence of PBDEs in the Philippine environment. Graphical abstract: Highlights: Review of PBDE occurrence in the Philippines, an e-waste receiving country Provides the first report on PBDE levels in market fish and particulate matter collected from Metro Manila Higher brominated PBDEs including BDE-209 were dominant in the Philippine market fish which differs from BDE profiles in US fish Predominant congeners in particulate matter samples were BDE-47, followed by BDE-99 and BDE-100 Additional studies on PBDE occurrence in the Philippines are needed